2018
DOI: 10.1038/s41393-017-0047-x
|View full text |Cite
|
Sign up to set email alerts
|

Provided support, caregiver burden and well-being in partners of persons with spinal cord injury 5 years after discharge from first inpatient rehabilitation

Abstract: High levels of perceived burden among partners and the associations between higher burden with lower well-being show the importance to prevent caregiver overload in partners of individuals with SCI. Monitoring burden during regular rehabilitation visits may help to early detect burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
1
27
0
1
Order By: Relevance
“…Persons with spinal cord injury (SCI), especially those with higher lesion levels, are dependent on care and assistance with daily living activities, with a majority provided by informal caregivers [1]. Caregiving carries a heavy objective and subjective burden [2, 3], which impacts the life of the informal caregiver [4]. The caregiving partners of persons with SCI reported a demand for external support [5].…”
Section: Introductionmentioning
confidence: 99%
“…Persons with spinal cord injury (SCI), especially those with higher lesion levels, are dependent on care and assistance with daily living activities, with a majority provided by informal caregivers [1]. Caregiving carries a heavy objective and subjective burden [2, 3], which impacts the life of the informal caregiver [4]. The caregiving partners of persons with SCI reported a demand for external support [5].…”
Section: Introductionmentioning
confidence: 99%
“…Families with TBI report high frequencies of anxiety and depression symptoms [17, 18], and high emotional burden [7, 13]. Similar results have been found among families living with tSCI [6, 19]. Furthermore, impaired quality of life (QoL) has been reported for both groups [5, 10, 12, 13, 16, 20], for as long as up to 20 years after injury [21].…”
Section: Introductionmentioning
confidence: 79%
“…[5]. Acquiring a traumatic injury not only has an impact on the survivor, but will also affect their families, as they will have to adapt to the changed life situation as well [6–8]. The consequences can affect the family early on [9, 10], but also long term [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems noteworthy that in our study the level of physical independence of the person with SCI or ABI was not found to be related with psychological distress, resilience, appraisals and coping. However, also in previous studies no strong relationships were found between physical independence of the patient and anxiety, depression or mental health of caregivers [21,43]. This could indicates that the objective severity of disabilities is subordinate to the subjective experience of the situation [43].…”
Section: Mediation Modelmentioning
confidence: 74%